Verifying the accuracy of the TITAN Penning-trap mass spectrometer - Brodeur, Maxime; Brunner, Thomas; Gallant, Aaron; Simon, Vanessa Véronique (International journal of mass spectrometry, 2012)
TITAN (TRIUMF's Ion Traps for Atomic and Nuclear science) is an online facility designed to carry out high-precision mass measurements on singly and highly charged radioactive ions. The TITAN Penning trap has been built and optimized in order to perform such measurements with an accuracy in the sub ppb-range. A detailed characterization of the TITAN Penning trap is presented and a new compensation method is derived and demonstrated, verifying the performance in the range of sub-ppb.